Effects of Conserved Wedge Domain Residues on DNA Binding Activity of Deinococcus radiodurans RecG Helicase - Jeong, Sun-Wook; Kim, Min-Kyu; Zhao, Lei; Yang, Seul-Ki; Jung, Jong-Hyun; Lim, Heon-Man; Lim, Sangyong (Frontiers in Genetics, 2021)
Deinococcus radiodurans is extremely resistant to ionizing radiation and has an exceptional ability to repair DNA damage caused by various DNA-damaging agents. D. radiodurans uses the same DNA-repair strategies as other prokaryotes, but certain D. radiodurans proteins involved in the classical DNA repair machinery have characteristics different from their counterparts. RecG helicase, which unwinds a variety of branched DNA molecules such as Holliday junctions (HJ) and D-loops plays important roles in DNA repair, recombination, and replication. Primary sequence analysis of RecG from a number of bacterial species revealed that 3 amino acids (QPW) in the DNA-binding wedge domain (WD) are well conserved across the Deinococcus RecG proteins. Interactions involving these conserved residues and DNA substrates were predicted in modeled domain structures of D. radiodurans RecG (DrRecG). Compared to the WD of Escherichia coli RecG protein (EcRecG) containing FSA amino acids corresponding to QPW in DrRecG, the HJ binding activity of DrRecG-WD was higher than that of EcRecG-WD. Reciprocal substitution of FSA and QPW increased and decreased the HJ binding activity of the mutant WDs, EcRecG-WDQPW and DrRecG-WDFSA, respectively. Following γ-irradiation treatment, the reduced survival rate of D. radiodurans recG mutants (ΔrecG) was fully restored by the expression of DrRecG, but not by that of EcRecG. EcRecGQPW also enhanced γ-radioresistance of ΔrecG, whereas DrRecGFSA did not. ΔrecG cells complemented in trans by DrRecG and EcRecGQPW reconstituted an intact genome within 3 h post-irradiation, as did the wild-type strain, but ΔrecG with EcRecG and DrRecGFSA exhibited a delay in assembly of chromosomal fragments induced by γ-irradiation. These results suggested that the QPW residues facilitate the association of DrRecG with DNA junctions, thereby enhancing the DNA repair efficiency of DrRecG.